The Effect Of Nutritional Literacy On The Adequacy Of Energy And Protein In Culinary Education Study Program Students At Semarang State University - Hanapi, Roy; Fathonah, Siti (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2023)
Abstract The research objectives were 1) to determine the level of nutritional literacy in college students 2) to determine energy adequacy in college students 3) to determine protein adequacy in college students 4) to determine the effect of nutritional literacy on energy adequacy 5) to determine the effect of nutritional literacy on protein adequacy. This research was a survey research and a cross-sectional research design with research subjects being students of the Culinary Education Study Program, Semarang State University. Sampling used a saturated sampling technique in which all members of the population in this study were used as samples. The sample in this study was 81 students of the Culinary Education Study Program, Semarang State University, Class of 2021. Nutritional literacy is measured by The Nutrition Literacy Assessment Instrument (NLit). Energy and protein adequacy was measured using a food recall instrument for two days. Data analysis used percentage descriptive analysis for objectives 1-3 and simple linear regression for objectives 4-5. The results showed that the level of nutritional literacy on average was in the less category with a percentage of 63.4%. Energy adequacy shows an average value in the category of moderate level deficit with a percentage of 73%. Protein adequacy shows an average value in the mild deficit category with a percentage of 87.6%. The results of simple linear regression analysis showed that there was no significant effect between nutritional literacy and energy adequacy (p = 0.698) and there was no significant effect between nutritional literacy and protein adequacy (p = 0.812). These results indicate that students' understanding of nutritional literacy has not been able to fulfill proper nutritional adequacy. Keywords: Nutritional literacy, energy adequacy, protein adequacy